2016
DOI: 10.1111/cas.12863
|View full text |Cite
|
Sign up to set email alerts
|

Utility of epirubicin‐incorporating micelles tagged with anti‐tissue factor antibody clone with no anticoagulant effect

Abstract: Tissue factor (TF), an initiator of the extrinsic blood coagulation cascade, is overexpressed in different types of cancer. Tissue factor overexpression is also known as a poor prognostic factor in pancreatic cancer. We recently developed anti‐TF antibody (clone1849)‐conjugated epirubicin‐incorporating micelles (NC‐6300), and reported that this anti‐TF1849‐NC‐6300 showed enhanced antitumor activity against TF‐high expressed human pancreatic cancer cells, when compared with NC‐6300 alone. However, clone 1849 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…This anti-TF antibody-conjugate reduced the growth of BxPc-3 subcutaneous tumors but not SUIT2 subcutaneous tumors. 103 Three groups developed different anti-TF antibody conjugates with monomethyl auristatin E (MMAE). [104][105][106] MMAE inhibits cell division of actively dividing cells by blocking the polymerization of tubulin and shows an antitumor effect.…”
Section: Targeting Tissue Factor As a Novel Anticancer Therapymentioning
confidence: 99%
“…This anti-TF antibody-conjugate reduced the growth of BxPc-3 subcutaneous tumors but not SUIT2 subcutaneous tumors. 103 Three groups developed different anti-TF antibody conjugates with monomethyl auristatin E (MMAE). [104][105][106] MMAE inhibits cell division of actively dividing cells by blocking the polymerization of tubulin and shows an antitumor effect.…”
Section: Targeting Tissue Factor As a Novel Anticancer Therapymentioning
confidence: 99%
“…Previous reports have suggested that cytokine‐induced and/or chemokine‐induced TF expression in tumor cells and tumor‐connective tissues promotes neo‐angiogenesis, invasion, and metastasis in ovarian cancer . Recently, Matsumura's group . demonstrated that the systemic administration of selective anti‐TF antibody conjugated with an anti‐cancer drug was effective for growth inhibition of human pancreatic and gastric cancer cell lines using murine intravenous xenograft models without affecting coagulant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Non-specific binding was blocked by applying Block Ace reagent (Dainippon Pharmaceutical Co., Ltd., Osaka, Japan) with 10% goat serum for 30 min at room temperature. Cells were incubated with anti-TF antibody 1849 (rat IgG 2b ) (26,30) as a primary antibody overnight at 4˚C. A secondary anti-rat antibody conjugated with Cy3 (diluted 1:1,000; cat.…”
Section: Methodsmentioning
confidence: 99%